Diffusion model of interacting gravity waves on the surface of deep fluid - V. E. Zakharov; V. E. Zakharov; A. N. Pushkarev; A. N. Pushkarev (Nonlinear Processes in Geophysics, 1999)
A simple phenomenological model for nonlinear interactions of gravity waves on the surface of deep water is developed. The Snl nonlinear interaction term in the kinetic equation for wave action is replaced by the nonlinear second-order diffusion-type operator. Analytical and numerical studies show that the new model gives a reasonably good description of a real situation, consuming three order of magnitude less computer time.